Effects of Demographic and Academic Variables on Financial Behavior and Sources of Influence among College Students - Koirala, Kamal Bahadur (NPRC Journal of Multidisciplinary Research, 2025)
Background: Financial literacy is an essential skill for college students, but important gaps in knowledge exist regarding the influence of demographic and academic variables on financial behaviors and sources of learning. Existing research has suggested that gender, age, and area of study could affect financial choice-making, but evidence has been mixed, especially within multifaceted education settings. Objective: The aim of this study was to investigate the effect of gender, age, and study stream (Management versus Non-management) on two key areas of financial literacy: financial behavior (saving, budgeting, etc.) and perceived sources of financial influences (learning). Methods: A cross-sectional questionnaire was administered to 196 undergraduate students. Independent variables included gender (86 females, 110 males), age (M~22), and stream of education (149 Management, 47 Non-management). Dependent variables were composite measures of financial behavior and financial influences, measured via Likert scales. Data analysis employed independent samples t-tests, bootstrapping, correlation, and descriptive statistics in SPSS. Findings: Female students performed significantly higher on financial behavior (M=3.47, SD=0.80) than males (M=3.23, SD=0.71); t(194)=2.227, p=.027. There was no gender difference in financial influences significant (p=.254). There was a statistically significant but weak negative correlation between age and financial influences (r = -.178, p = .013), where older students reported learning less from formal influences. Age was not correlated with financial behavior at all (p=.540). The non-management students reported much higher financial influences (M=3.12, SD=0.52) than management students (M=2.86, SD=0.57), with non-overlapping bootstrap confidence intervals. There was a trend towards better financial behavior for non-management students, but more testing is required. Conclusion: The study concludes that gender and academic stream are good predictors of the aspects of financial literacy while age is not a significant factor. Women exhibit more active financial behaviors, and non-management students report acquiring greater knowledge from their learning sources, disproving stereotypes about management students' readiness in finances. Implication: University administrators and education in finance would have to design targeted interventions. Male students' intervention programs would aim at establishing core financial habits, while management courses would support more explicitly the importance of their finance content in order to enhance the students' perception of their learning.